TRACING THE HISTORY OF ALADDIN LIVE-ACTION MOVIE (2019): A NEW HISTORICISM STUDY - Hanifah, Asmaa; Trisnawati, Ririn Kurnia; Agustina, Mia Fitria (UIN Alauddin Makassar, 2022)
The objectives of this research are to find the differences and the causes of the changed character and setting of places in Aladdin live-action movie and The Story of Ala-ed-Din and the Wonderful Lamp (TSAWL) short story by Antonie Galland. Also, it aims at analyzing the purposes of such changes. The study is qualitative-based research, and the analysis was done by examining the intrinsic parts of the works, such us characters and the setting of places. The extrinsic approaches were employed where New Historicism was needed as a theoretical framework. The results show that the reconstruction of the character Aladdin and changing the setting of place from China to a fictional place, a city of Agrabah obviously occurs. It can be concluded that the changed has been caused by the time the story is made and the author to make the movie live in the year of its creation.